DEMOCRACY AND THE 1945 CONSTITUTION: A POLITICAL PERSPECTIVE ON INDONESIA’S CONSTITUTIONAL FRAMEWORK - I Made Sila; I Gusti Ngurah Santika; Daniel Ndara Kandi; Carolina R. K. D Ngana (CV. Tirta Pustaka Press, 2025)
This article examines the evolution and role of Indonesia’s 1945 Constitution in shaping the country’s democratic governance from a political perspective. Following the reformation era, constitutional amendments were enacted to transform Indonesia from an authoritarian regime into a democratic state by establishing direct presidential elections, strengthening legislative authority, guaranteeing human rights, and creating independent institutions such as the Constitutional Court and the Corruption Eradication Commission. Using a qualitative normative approach and political-legal analysis, this study explores how these constitutional reforms have redefined power relations and institutional functions within Indonesia’s political system. While the amended Constitution provides a solid legal framework for democracy, challenges remain in its implementation, including political elite interests, institutional weaknesses, and ongoing attempts to manipulate constitutional norms. The findings suggest that the sustainability of Indonesian democracy depends not only on the constitutional text but also on political actors’ commitment, judicial independence, and active civil society participation. This article contributes to the understanding of constitutional democracy as a dynamic process influenced by both legal frameworks and political realities.